Avatar Embodiment. Towards a Standardized Questionnaire. - Gonzalez Franco, Mar; Peck, Tabitha C (Frontiers in Robotics and AI, 2018)
Inside virtual reality, users can embody avatars that are collocated from a first-person perspective. When doing so, participants have the feeling that the own body has been substituted by the self-avatar, and that the new body is the source of the sensations. Embodiment is complex as it includes not only body ownership over the avatar, but also agency, co-location, and external appearance. Despite the multiple variables that influence it, the illusion is quite robust, and it can be produced even if the self-avatar is of a different age, size, gender, or race from the participant’s own body. How do we measure Embodiment of Avatars? Embodiment illusions are the basis for many social VR experiences and a current active research area among the community. Researchers are interested both on the body manipulations that can be accepted, as well as on studying how different self-avatars produce different attitudinal, social, perceptual, and behavioural effects. However, findings suggest that despite embodiment being strongly associated with the performance and reactions inside VR, the extent to which the illusion is experienced varies between participants. Towards a standard questionnaire We reviewed the questionnaires used in past experiments and propose a standardized embodiment questionnaire based on 25 questions that are prevalent in the literature. Find the complete review in this publication: Gonzalez-Franco M and Peck TC (2018) Avatar Embodiment. Towards a Standardized Questionnaire. Front. Robot. AI 5:74. doi: 10.3389/frobt.2018.00074 We encourage future VR experiments that include first-person virtual avatars to administer this questionnaire in order to evaluate the degree of embodiment. Download the questionnaire here: Embodiment_questionnaire.docx If you use this questionnaire, please cite: Gonzalez-Franco M & Peck TC (2018) Analysis We propose that the values be aggregated using Principal Component Analysis (PCA), we provide a sample ipython code on how to complete the embodiment PCA. It can be cloned and run for free directly in Microsoft Azure Notebook by any researcher. https://notebooks.azure.com/margon/libraries/EmbodimentQuestionnairePCA Note that body ownership, agency and body location are the most relevant aspects of the embodiment illusion.